POTENSI RETRIBUSI PARKIR DI KABUPATEN PEKALONGAN - Choliq Sabana; Catur Ragil Sutrisno (LPPM Universitas Pekalongan, 2013)
This study aims to analyze contribution of parking retribution for local revenue, the potential of parking retribution, and identifying the factors supporting and inhibiting acceptance roadside parking retribution general and special place. Research utilizes mixed method, which is research which utilize quantitative method and kualitative. Observational object is parking retribution at common wayside and special place parking retribution. There is location even research covers 135 dot park at common wayside and 50 dot park special places. The analysis shows the average contribution of PAD to the revenues Pekalongan’s Regency 7.92%, lower than the average contribution of PAD to Revenue in the City / County in Indonesia which amounted to 12%. Levies a major contribution to regional income, ranging from 71%. Retribution parking can be a source of revenue given the potential for the development of demographic, socio- economic, as well as the growth of vehicle ownership. Opportunities to increase revenue is still open considering parking retribution labor income is higher than the parking lot UMK of Central Java, and the growth of new parking base. Keywords: potential, parking retribution, PAD.